Comparing the Effectiveness of Resilience Training and Acceptance and Commitment Group Training on Quality of Life in Students from Divorced Families, Controlling for Age at Divorce and Time Since Divorce - Ansari, Zohre; Atashafrouz, Askar; Behroozi, Nasser (Applied Family Therapy Journal (AFTJ), 2025)
Objective: This study aimed to compare the effectiveness of resilience training and acceptance and commitment group training on improving quality of life in male students from divorced families, while controlling for age at the time of parental divorce and the duration since the divorce.Methods and Materials: This quasi-experimental study was conducted on 90 male students in grades 5 to 9 from Kouhchenar County, whose parents were divorced. Participants were selected using convenience sampling from six schools with the highest prevalence of students from divorced families and were randomly assigned to three groups: resilience training (n = 30), acceptance and commitment training (n = 30), and control (n = 30). The interventions included ten 50-minute weekly sessions based on Kruger’s (2006) resilience protocol and eight weekly sessions based on Hayes and Rose’s (2008) ACT protocol. All participants completed the WHOQOL-BREF before the intervention, immediately after, and at a one-month follow-up. Data were analyzed using repeated measures ANOVA and MANCOVA while adjusting for confounding variables.Findings: Significant improvements were observed in all four domains of quality of life—physical health, psychological health, social relationships, and environmental health—in both intervention groups across time (p < 0.001). The time × group interaction effect was also significant for all components (p < 0.001). Between-subjects analysis showed significant differences in posttest mean scores among the three groups (p < 0.001), and Bonferroni post hoc comparisons confirmed that both experimental groups outperformed the control group (p < 0.001), with the ACT group showing significantly greater improvements than the resilience group in all domains (p < 0.001).Conclusion: Both resilience training and ACT-based group training effectively enhanced the quality of life of students from divorced families; however, ACT demonstrated superior and more sustained improvements. These findings highlight the potential of ACT as a preferred school-based intervention for adolescents coping with familial disruption.